Leading and Managing Professional Services Firms in the Infrastructure Sector - Ellis, Tim (Boca Raton, FL : CRC Press, 2018)
"Professional services firms play a vital role in the social, environmental and economic well-being of any economy. This book considers the key skills and elements required to successfully lead and manage a professional services firm operating in the infrastructure sector. Public- and private-sector clients recognise the role that infrastructure plays in the functionality of our cities and that most urban conurbations have a backlog of infrastructure to deliver to meet the needs of increasing populations, greater urbanisation and emerging economies. Just keeping pace with projected global GDP growth will require an enormous investment in infrastructure and skilful leadership to deliver it. In response to this challenge, professional services firms will need to be well-led and well-managed to be successful and sustainable in the long-term. Such organisations must provide high-value advice, design, knowledge and innovations to get more out of the existing assets and to plan and design new assets with greater integrity and construct them more productively, efficiently and effectively. This book provides practical frameworks for emerging operational managers and future project leaders to prepare them to successfully manage these firms and deliver such projects in the face of new and often disruptive technologies and shifting corporate landscapes.The book is essential reading for aspiring leaders operating in all infrastructure market sectors including energy, water, sewerage, road, rail, ports, airports, education, health, justice, retail, entertainment, property and development sectors."--Provided by publisher.
chapter 1 Introduction / Ellis Tim -- chapter 2 Strategy / Ellis Tim -- chapter 3 The nature of the firm / Ellis Tim -- chapter 4 Marketing and communications / Ellis Tim -- chapter 5 Business development / Ellis Tim -- chapter 6 Winning proposals / Ellis Tim -- chapter 7 Growth through mergers and acquisitions / Ellis Tim -- chapter 8 Project management / Ellis Tim -- chapter 9 Operational management / Ellis Tim -- chapter 10 Commercials / Ellis Tim -- chapter 11 Contracts / Ellis Tim -- chapter 12 Risks and opportunities / Ellis Tim -- chapter 13 Knowledge management / Ellis Tim -- chapter 14 People and culture / Ellis Tim -- chapter 15 Business systems and processes / Ellis Tim -- chapter 16 How to increase the chance of project success / Ellis Tim.
Keywords: Construction industry -- Management; Engineering -- Management; Production management; Project management; CivilEngineeringnetBASE; Construction Business Management; Engineering Management; Engineering Project Management; ENGnetBASE; Operations Management; Project Management; SCI-TECHnetBASE; STMnetBASE